Operations analysis using Microsoft Excel - Weida, Nancy C., 1959-; Richardson, Ronny; Vazsonyi, Andrew (Pacific Grove, CA : Duxbury, 2001)
This book concentrates on the quantitative aspects of operations management, while covering only those features of Excel that are of interests to operations management and for which Excel is an excellent modeling tool.
Keywords: Computer; Microsoft Excel for Windows; Production management; Production management; Microsoft Excel for Windows; Electronic spreadsheets